Observation, evaluation and coaching: the local orderliness of 'seeing' performance. Issue 3 (23rd March 2020) - Corsby, Charles L. T.; Jones, Robyn L.
ABSTRACT: Inspired by ethnomethodological attention to social order, the aim of this paper was to examine the visible, tangible and contextual details of how coaches' observations, or what coaches actually see, are accomplished in practice. Drawing upon examples from a season long ethnomethodologically informed ethnographic investigation of a semi-professional football club, the paper positions coach observation, not as a visual perception, but as a locally organised achievement of the individuals involved. In doing so, attention is paid to the details of observations constructed in, through and by coaches, assistants and players. The paper concludes with some tentative recommendations for related progressive practice.